2018
DOI: 10.4149/neo_2018_170318n194
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of Cyfip1 may be a potential biomarker in nasopharyngeal carcinoma

Abstract: Cytoplasmic FMR1 interacting protein 1 (Cyfip1) is a new candidate tumor suppressor gene, which may play an impor- tant role in the occurrence and development of cancers. However, the role of Cyfip1 in nasopharyngeal carcinoma (NPC) remains poorly known. The aim of this study was to investigate the Cyfip1 mRNA expression in NPC and its association with clinicopathological features. The study population comprised 114 Chinese individuals, including 69 NPC tissues and 45 non-cancerous nasopharyngeal tissues. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The activation of oncogenes and deletion of cancer suppressor genes are considered to be important factors in the development of NPC [8][9][10]. In recent years, a number of literatures have reported that the expression levels of tumor suppressor genes were related to the occurrence and development of NPC.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of oncogenes and deletion of cancer suppressor genes are considered to be important factors in the development of NPC [8][9][10]. In recent years, a number of literatures have reported that the expression levels of tumor suppressor genes were related to the occurrence and development of NPC.…”
Section: Discussionmentioning
confidence: 99%
“…CYFIP1 may play an important role in the occurrence and development of cancers. Loss of CYFIP1 expression has been found in a number of human cancers, including breast cancer, colon cancer, lung cancer, bladder cancer, cutaneous squamous cell carcinoma, nasopharyngeal carcinoma, and acute lymphoblastic leukemia [38][39][40][41]. CYFIP1 expression was correlated with tumor progression in epithelial cancers and it raised the possibility that loss of CYFIP1 might correlate with clinical outcome [39].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that CYFIP1 was commonly deleted and associated with poor prognosis during invasion of epithelial tumors. 14 CYFIP1 was a new candidate tumor suppressor gene in nasopharyngeal carcinoma 15 and was controlled by NOTCH1 signal in squamous cell carcinoma of the skin. 16 Nevertheless, CYFIP2 has yet to be thoroughly explored, particularly its association with human cancer has yet to be conducted.…”
Section: Introductionmentioning
confidence: 99%